Sensitivity Analysis of Biosensor-Based SiGe Source Dual Gate Tunnel FET Having Negative Capacitance - Dipshika Das; Rudra Sankar Dhar; Pradip Kumar Ghosh; Yash Sharma; Amit Banerjee (IEEE Access)
This work proposes a unique design of charge plasma based junctionless SiGe source TFET with dual cavity and ferroelectric gate dielectric. The biosensor works on the principle of dielectric modulation for label-free detection, where the cavity lies under the source and gate metal just around the tunneling junction of the dual gate TFET. Nanocavity above the source and gate regions act as reservoir of biomolecules (to be detected) around the tunneling junction, letting the drain current modulate. Cavity dimensions and its placement have been optimized to achieve better current sensitivity. Dual gate architecture with laterally split dielectric is used to overcome the short channel impact and to enhance the current ratio. The biosensor can recognize neutral, positive, and negative charges with the highest drain current sensitivity and ION/IOFF ratio for biomolecule gelatin. It engages the principle of negative capacitance for better subthreshold swing and ON current for identification of biomolecules such as gelatin (k = 12), keratin (k = 8), streptavidin (k = 2.1), bacteriophage T7 (k = 6.3), and APTES (k = 3.57) at low voltage biasing. Finally, RF analyzes are carried out to explore the benefits of using negative capacitance where the biosensor acts as an intrinsic voltage amplifier exhibiting superior gain-bandwidth product (GBP) and cut-off frequency (fT), indicating its potential for high-speed operation and real-time sensing applications. The research yields repeatable outcomes for several calculated analyses.